Psikoedukasi homesick santri di Ummul Mukminin Makassar - Eva Meizara Puspita Dewi; Muhammad Nur Hidayat Nurdin (Universitas Negeri Makassar, 2020)
The Homesick issue was raised as the focus of these community service activities because the results of the survey showed that the problem of homesickness were still considered by 8th and 9th grade students. The assumptions of this uncomfortable feeling have long been corrected by the students and it needs special improvement. The number of participants in this study are 186 students. The method used are open questionnaire to describe the homesickness of the students, pretest, psychoeducation, focuss group discussion, poster competition, and post-test. The result indicates that it seems the students of the Islamic Boarding School Ummul Mukminin and Meanwhile, they feel comfortable being at boarding school. The pre-test shows that there is a decrease in the level of homesickness for students after participating in psychoeducation activities by comparing the number of pretest and posttest per class. The number of students in high level has become moderate even low, and moderate level has become low.